Engaging in a New Field: Business-Owning Families’ Differential Approach to Impact Investing - Cruz, Cristina; Justo, Rachida; Roche, Jeanne (Instituto de la empresa familiar, 2021)
We develop a theoretical framework explaining why and how business-owning families (BOF) engage in impact investing. Despite its exponential growth, the burgeoning field of impact investing is still subject to competing interpretations and varying practices. Building on the framework proposed by Nason et al. (2019b), we argue that a businessowning family’s frame of reference (backward vs. forward-looking and internally vs. externally oriented) constitutes a relevant heterogeneity that triggers a unique driver for engaging in impact investing and a distinct set of practices to do so.
Keywords: Business-owning family; Impact investing; Venture philanthropy; Socioemotional wealth; Reference point